Conclusion (Archives of Criminology, 1972)
In the light of the surveys of the 15 - l7-year-olds “out of school and out of work,” it can be seen that a large majority of the subjects are recruited from among boys and girls whose basic problems can be reduced to school maladjustment, serious learning difficulties and inability to adapt to the school curriculum. With most of the subjects social maladjustment is clearly connected with school maladjustment, which is no doubt frequently the anterior process.The lack of detailed psychological and medical tests makes it impossible to say what are the factors chiefly responsible fur such school retardation: what percentage of the subjects are backward children, children with only partial developmental retardation, children with certain congenital defects which are serious obstacles to learning to read and write, or children with personality disorders which interfere considerable with a normal process of education, reduce theircapacity for systematic effort, impede concentration, etc.The children whose normal progress at school encounters serious difficulties and cannot cope unaided with their school obligations have a sense of inferiority with regard to the other children in their class, and the conflict situations experienced by them continually and their fear of the consequences of bad results at school make for a hostile attitude to school, truancy, seeking contacts outside school with peers in a similar position, spending much of their time with other maladjusted boys in whose company they can win approval. Children of this kind frequently drop far behind in elementary school and sometimes fail to complete it altogether. Subsequently, they have a very difficult start in life, extremely limited prospects of employment in jobs with a low social status and a sense of personal failure and rejection which frequently helps to develop antisocial attitudes.In dealing with boys and girls of this sort who have already reached an older age bracket, one should realize that their considerable school retardation, their unaccustomedness for systematic study and the development of certain adverse habits militate against progress in the vocational schools to which they are directed. In view of the fact that teaching them a specific trade in combination with practical         in-work training may be of vital importance to their subsequent careers, the syllabus in these special vocational schools should be adjusted to the degree of inability displayed by such boys and girls. Since the boys who have not even completed six or seven grades of elementary school are in a worse position than those who have completed a greater number of grades, the syllabus of the vocational courses for these children should be differentiated to match their achievement level in elementary school. It seems essential therefore, before directing such boys and girls to a vocational school, to submit them to psychological tests to discover their intelligence level and suitability for a specific trade.The findings of these surveys make clear the importance from the point of view not only of the practice of the educational authorities but also of social policy of paying special attention to cases of recurring repetition of elementary school grades and truancy, and of failure to complete elementary school. Problems and failures at school require the early intervention of psychologists and doctors and the extension of special attention to such children in the earliest grades. The elimination and prevention of symptoms of school maladjustment depend on the proper organization of school work to allow for the specific problems of this category of children. It is essential to provide a sufficient number of special classes in the lower years to enable children making poor progress to catch up and also individual coaching of pupils who have special learning problems.The surveys show how important the implementation of the above recommendations could be for prevention of social maladjustment and demoralization among a large proportion of the children subsequently classified as “out of school and out of work”. The fact that among juvenile offenders there is a large incidence of records of serious disturbances in the course of their education from an early age is obvious evidence of the need to pay special attention to school maladjustment with a view to the prevention of juvenile delinquency.Since the surveys have shown that a large proportion of children with serious school failures come from adverse home backgrounds, from broken homes, from homes in which the father is an alcoholic and from homes whose material circumstances are bad, it is essential to put such families under special supervision and also to provide welfare benefits to the mothers of children in such home.